TIPping the scales towards greater employment chances? Evaluation of a Trial Introduction Program (TIP) for newly-arrived immigrants based on random program assignment - Pernilla Andersson Joona; Lena Nekby (Institute for the Study of Labor (IZA), 2009)
A Trial Introduction Program (TIP) for newly-arrived immigrants to Sweden was implemented from October 2006 to June 2008 in order to meet the main criticisms directed at existing introduction programs. Two primary innovations were introduced, flexible language instruction parallel with other labor market activities at the Public Employment Service (PES) and intensive counseling and coaching by PES caseworkers with considerably reduced caseloads. Within participating municipalities, newly-arrived immigrants were randomly assigned into TIP (treatment) or regular introduction programs (control). Results indicate significant treatment effects on the probability of attaining regular employment as well as the probability of entering intermediate PES training programs. Hazard rates into PES training programs were also significantly higher for participants in TIP in comparison to participants in regular introduction programs.
urn:nbn:de:101:1-2009033055
Keywords: J15; J64; J68; J61; C41; 330; Labor market policy evaluation; integration; introduction programs; experiment; Arbeitsmarktpolitik; Wirkungsanalyse; Migranten; Berufliche Integration; Soziale Integration; Schweden